Pola Konsumsi Pangan Penyandang Disabilitas di Kota Malang - Agustina Shinta (The Center for Disability Studies and Services Brawijaya University, 2014)
This research aims to (1) identify indicators of food and nutrition on people with disabilities, and (2) to analyze the pattern of diversification of persons with disabilities. Identification of indicators using the Recommended Daily Intake of energy, protein, fat, carbohydrates and Micronutrients (Ca, F, Fe and vitamin C), while the diversification pattern analysis method using the analysis of Dietary Pattern Hope. The results showed that (1) persons with disabilities in Malang meet the Recommended Daily Intake of energy, carbohydrates and Micronutrients for iron and phosphorus, but the excess in the Recommended Daily Intake of fat and deficient in the Recommended Daily Intake for protein, vitamin C and calcium; (2) persons with disabilities in Malang is in diversification in groups of oils and fats, but shortages in fish and sea food groups.